REVIEW: Viorica Marian, 2024, Puterea limbajului. Cum ne transformă mintea codurile pe care le folosim pentru a gândi, a vorbi, a trăi. Translated by Iulian Comănescu, Bucharest: Editura Humanitas - Marinușa CONSTANTIN (Diversitate si Identitate Culturala in Europa, 2025)
This review of Puterea limbajului. Cum ne transformă mintea codurile pe care le folosim pentru a gândi, a vorbi, a trăi (original English title The Power of Language: How the Codes We Use to Think, Speak, and Live Transform Our Minds), authored by the psycholinguist Viorica Marian, aims to highlight the cognitive particularities of multilingual speakers, as revealed through experimental studies and tests – especially those employing eye-tracking technologies – conducted over the years on multilingual subjects. Moreover, Marian’s study innovatively addresses the evolution of communication codes in the context of contemporary technological advancements.